2017
DOI: 10.1021/acs.nanolett.7b00183
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Nonplasmonic Nanoparticles for Efficient Temperature-Feedback Optical Heating

Abstract: We propose a novel photothermal approach based on resonant dielectric nanoparticles, which possess imaginary part of permittivity significantly smaller as compared to metal ones. We show both experimentally and theoretically that a spherical silicon nanoparticle with a magnetic quadrupolar Mie resonance converts light to heat up to 4 times more effectively than similar spherical gold nanoparticle at the same heating conditions. We observe photoinduced temperature raise up to 900 K with the silicon nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
136
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 49 publications
9
136
0
1
Order By: Relevance
“…Zograf et al recently demonstrated that in Si nanoparticles the optical field localization at magnetic quadrupolar resonance is able to generate a remarkable optical heating, despite its imaginary part of refractive index is two orders of magnitude lower than that of metals. 28 Our study corroborates those observations and provides new insights into opto-thermal management of Si-based systems, demonstrating that the local heating can be increased beyond the melting point of refractory materials. On the other hand, we also demonstrated that thermally-robust beads with outstanding…”
supporting
confidence: 85%
“…Zograf et al recently demonstrated that in Si nanoparticles the optical field localization at magnetic quadrupolar resonance is able to generate a remarkable optical heating, despite its imaginary part of refractive index is two orders of magnitude lower than that of metals. 28 Our study corroborates those observations and provides new insights into opto-thermal management of Si-based systems, demonstrating that the local heating can be increased beyond the melting point of refractory materials. On the other hand, we also demonstrated that thermally-robust beads with outstanding…”
supporting
confidence: 85%
“…All‐dielectric NPs and nanostructures promote optical field localization near the surface and redirection of light to biomolecules that interact poorly with light. It also should be noted that such NPs are promising candidates for bioimaging , biosensing and heat therapy . In addition, most all‐dielectric NPs are rapidly bio‐degradable and relatively non‐toxic .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, most all‐dielectric NPs are rapidly bio‐degradable and relatively non‐toxic . However, few available reports on biophotonic applications of such NPs have not addressed potential conformational changes in biomolecules adsorbed on their surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such nanostructures have recently revealed many features, which previously were available only for the plasmonic counterparts. Examples include single-molecule sensing [5,6], efficient harmonic generation [7][8][9], and, among others, photothermal activity [10]. This progress has stimulated the development of all-dielectric photonic devices, including nanoantennas, metasurfaces and optical interconnects [1,3,4].…”
Section: Introductionmentioning
confidence: 99%